The The development of the educational institutions in the social transformation process: From the High School Colegio de Bachilleres of the Chihuahua state, Mexico (1973-1985) - Salcido Sáenz, Marilyn Georgia; Trujillo Holguín, Jesús Adolfo (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2020)
This article analyzes the influence of educational institutions to conceive social transformations based on the effectiveness of the school in spawning a school culture of its own. Particularly, it is studied the creation of the upper secondary level subsystem of the Colegio de Bachilleres del Estado de Chihuahua (COBACH) from 1973 to 1985. The present work is part of an ongoing doctoral research, which aims at the historical reconstruction of the institution. In order to develop this article, oral and archival data were used for a reliable saving of the facts. It is taken a theoretical approach of the micro-historical analysis from the rescue of the regional institutional history with a human sense, it was based on the testimonies of its founders. It is emphasized in the first twelve years of the High School because during this period it was achieved a consolidation which shows how educational institutions are able of generating its own cultures.